2012
DOI: 10.1021/ie300510n
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Charge Separation in Nanostructured TiO2 Materials for Photocatalytic and Photovoltaic Applications

Abstract: Titanium dioxide (TiO 2 ) has been extensively investigated in solar energy applications, including heterogeneous photocatalysis and photovoltaics. For most TiO 2 materials, charge recombination between photoexcited electrons and holes severely limits the efficiencies of solar energy conversion. Different strategies have been attempted to improve charge separation in TiO 2 materials. This review focuses on three effective approaches to achieve enhanced charge separation by constructing mixed-phase TiO 2 , high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 114 publications
0
57
0
1
Order By: Relevance
“…By contrast, the brookite phase or anatase-brookite mixed phase is much less studied as a photocatalyst for CO 2 photoreduction, probably due to the previous difficulty in synthesizing high quality brookite nanocrystallites. The studies on pure phase TiO 2 show that anatase phase is more photocatalytically active than rutile, possibly attributed to the combined effect of lower recombination rate of electronhole pairs and higher surface adsorptive capacity (Hurum et al, 2003;Li and Gray, 2007;He et al, 2012). Recently, the much less studied brookite phase was found to have a catalytic activity similar to anatase but higher than rutile for CO 2 photoreduction with H 2 O .…”
Section: Effect Of Crystal Phasementioning
confidence: 99%
“…By contrast, the brookite phase or anatase-brookite mixed phase is much less studied as a photocatalyst for CO 2 photoreduction, probably due to the previous difficulty in synthesizing high quality brookite nanocrystallites. The studies on pure phase TiO 2 show that anatase phase is more photocatalytically active than rutile, possibly attributed to the combined effect of lower recombination rate of electronhole pairs and higher surface adsorptive capacity (Hurum et al, 2003;Li and Gray, 2007;He et al, 2012). Recently, the much less studied brookite phase was found to have a catalytic activity similar to anatase but higher than rutile for CO 2 photoreduction with H 2 O .…”
Section: Effect Of Crystal Phasementioning
confidence: 99%
“…Owing to some outstanding properties (high photo and chemical stability, photocatalytic activity, low cost, and nontoxicity), it is frequently used in photocatalytic removal of organic contaminations [1], hydrogen generation based on the water splitting process [2,3], solar cells [4], and biomedical devices [5]. In 1999, Zwilling et al [6] first reported the electrochemical formation of the self-assembled, highly ordered arrays of TiO 2 nanotubes via the anodization process of a titanium metal plate.…”
Section: Introductionmentioning
confidence: 99%
“…In photovoltaic applications, quantum dot (QD)-sensitized photoelectrodes have been widely investigated due to their importance in light absorption and charge transfer [1][2][3][4][5][6][7][8]. The photoelectrodes are typically TiO 2 films due to their non-toxic property and outstanding chemical stability [9].…”
Section: *Manuscript Click Here To View Linked Referencesmentioning
confidence: 99%